Pulmonary Vein Isolation with the Cryoballoon Technique: Feasibility, Procedural Outcomes, and Adoption in the Real World: Data from One Shot Technologies TO Pulmonary Vein Isolation (1STOP) Project. Issue 1 (22nd December 2016) - PADELETTI, LUIGI; CURNIS, ANTONIO; TONDO, CLAUDIO; LUNATI, MAURIZIO; PORCELLINI, STEFANO; VERLATO, ROBERTO; SCIARRA, LUIGI; SENATORE, GAETANO; CATANZARITI, DOMENICO; LEONI, LOIRA; LANDOLINA, MAURIZIO; DELISE, PIETRO; et al.
Abstract : Background: Catheter ablation (CA) is recommended for patients with drug refractory symptomatic atrial fibrillation (AF). "One Shot" catheters have been introduced to simplify CA and cryoballoon ablation (CBA) is spreading rapidly. Few real‐world data are available on standard clinical practice, mainly from single‐center experience. We aimed to evaluate clinical settings, demographics, and acute procedural outcomes in a large cohort of patients treated with CBA. Methods: A total of 903 patients (73% male, mean age 59 ± 11) underwent pulmonary vein CBA. Correlations between the patient's inclusion time and clinical characteristics, procedure duration, acute success rate, and intraprocedural complications were evaluated. Results: Seventy‐seven percent of patients were affected by paroxysmal AF and 23% by persistent AF. Overall, acute success rate was 97.9% and periprocedural complications were observed in 35 (3.9%) patients, 13 (1.4%) of which were classified as major complications. With respect to the patient's inclusion time analysis, an increase in treatment of persistent AF was observed, a significant decrease in CBA times (procedure, ablation, and fluoroscopy: 136.0 ± 46.5 minutes, 28.8 ± 19.6 minutes, and 34.3 ± 15.4 minutes, respectively) was observed, with comparable acute success rate and intraprocedural complications over time. The rate of major complications was extremely low (1.4%); no death, atrioesophageal fistula, stroke, or other major periinterventional or late complications occurred. Conclusion: This series represents the largest experience of CBA in the treatment of AF that also describes the adoption curve of this relatively recent technology. CBA showed an excellent safety profile when performed in a large real‐world clinical setting, with satisfactory acute success rate and, on average, short procedural times. Clinical Trial Registration: clinicaltrials.gov (NCT01007474)